State of hydrogen sulfide system in the rats brain under combined hyperhomocysteinemia and its correction - Zaichko, Natalia V.; Yurchenko, Peter A.; Filchukov, Denis A. (Journal of Education, Health and Sport, 2015)
Zaichko Natalia V., Yurchenko Peter A., Filchukov Denis A. State of hydrogen sulfide system in the rats brain under combined hyperhomocysteinemia and its correction. Journal of Education, Health and Sport. 2015;5(3):183-188. ISSN 2391-8306. DOI: 10.5281/zenodo.16349 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A183-188 https://pbn.nauka.gov.pl/works/549846 http://dx.doi.org/10.5281/zenodo.16349 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. STATE OF hydrogen SULFIDE SYSTEM IN the rats brain UNDER COMBINED hyperhomocysteinemia and its CORRECTION Natalia V. Zaichko, Peter A. Yurchenko, Denis A. Filchukov Department of biological and general chemistry, National Pirogov Memorial Medical University, Vinnytsya, Ukraine Abstract The state of hydrogen sulfide (H2S) system was investigated in the brain of rat under combined hyperhomocysteinemia (HHC) and its correction by betaine, vitamins B6, B9, B12 and trace element complex Esmin. Animals hold 14-days on starch-casein diet with 1% methionine in the absence of vitamins B6, B9, B12 caused increase in homocysteine serum to 12.0 times. Combined HHC induced significant decrease in H2S content and inhibition of H2S-synthesizing enzymes in rat’s brain. Normalization of diet, administration of vitamins B6, B9, B12 and Esmin for 7 days caused a decrease in serum homocysteine and increasing H2S content in rat brain. Betaine administration also decreased HHC and but the effect on H2S system in rat brain was not significant. Keywords: homocysteine, hydrogen sulfide, enzymes, metabolism, brain, betaine, vitamins, trace element complex.